2021
DOI: 10.18699/ssmj20210202
|View full text |Cite
|
Sign up to set email alerts
|

Changes in event-related synchronization/desynchronization of brain electric activity in cardiosurgical patients with postoperative cognitive dysfunction

Abstract: Aim of the study was to analyze the event-related synchronization/desynchronization of brain electrical activity during visual selection task in patients underwent on-pump coronary artery bypass grafting (CABG) with and without postoperative cognitive dysfunction (POCD). Material and methods. The study included 32 men who underwent on-pump CABG, mean age 57.2 ± 6.08 years. All patients carried out extended neuropsychological testing, a multi-channel computer electroencephalography (EEG) 3-5 days before CABG an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 32 publications
0
1
0
Order By: Relevance
“…There have been studies that have shown a reduced theta response in older adults with cognitive decline [39]. An analysis of event-related theta synchronization/desynchronization in cardiac surgery patients found that they exhibited less theta desynchronization in the left frontal-center region compared to patients without cognitive decline [40].…”
Section: Discussionmentioning
confidence: 99%
“…There have been studies that have shown a reduced theta response in older adults with cognitive decline [39]. An analysis of event-related theta synchronization/desynchronization in cardiac surgery patients found that they exhibited less theta desynchronization in the left frontal-center region compared to patients without cognitive decline [40].…”
Section: Discussionmentioning
confidence: 99%